Pemanfaatan Konsep Finite State Automata Pada Sistem Perparkiran Kendaraan Bermotor Bandara Raja Haji Fisabilillah Tanjungpinang - Dwi Nurul Huda; Amalia Zahara; Danil Hardinata (Jurnal Bangkit Indonesia, 2023)
Parking for motorized vehicles at airports is very important because airports are busy places with high mobility and a large number of passengers and vehicles. With adequate parking space, passengers and visitors can easily find a safe and comfortable parking space for their vehicles, so they can travel in peace and not need to stress over the well-being of their vehicles. In addition, parking lots for motorized vehicles at airports are also very important in maintaining the smooth flow of traffic and avoiding congestion in the airport area. With sufficient motorized vehicle parking, visitors can park their vehicles in an orderly manner and not cause congestion on the road or parking area. The motorized vehicle parking system at Raja Haji Fisabilillah Airport Tanjungpinang will be the focus of this study, which aims to implement the Finite State Automata idea. The research methodology includes Finite.State.Automata Vending Machines, Vending.Machine System Design and Motorized Vehicle Parking Vending Machine Designs. The results showed that the application of FSA to the motorized vehicle parking system can expand the effectiveness and exactness of the stopping framework at Raja Haji Fisabilillah Airport Tanjungpinang. In conclusion, it can be concluded that FSA can be applied to Vending Machines for motorized vehicle parking systems and can be a solution to increase the efficiency and accuracy of parking systems at Raja Haji Fisabilillah Airport Tanjungpinang. To improve the parking system's efficiency and accuracy, it is suggested that additional research be conducted on creating a motorized vehicle parking system using cutting-edge features.